How bad is Divergence in the Euro-Zone? Lessons from the United States of America and Germany - Sebastian Dullien; Ulrich Fritsche (Hamburg University, Department Economics and Politics, 2006)
This paper compares relative unit labour cost developments in the countries of the euro-area since the beginning of the European Monetary Union (EMU) both with historical developments and with intra-regional unit labour cost developments in the United States of America and Germany. To this end, unit labour cost indices for the US states and census regions from 1977 to 1997 as well as for the German Länder from 1970 to 2004 have been constructed. Against this benchmark, it is found that unit labour cost increases since 1999 in Portugal and to a lesser extent in Spain and Greece can be judged as excessive, pointing at labour market rigidities which might impair smooth working of EMU in the future.
Keywords: F2; F4; N2; 330; Unit labor costs; divergence; convergence; Euro-zone; inflation